4-H Volunteer Training Series—4-H Cloverbuds Program: 4-H for Younger Members - Amanda Squitieri; Sarah Hensley (EDIS)
Florida 4-H programs offered to children ages 5 to 7 are called 4-H Cloverbud programs and are a component of the Florida 4-H Youth Development Program. The goal of the Florida 4-H Cloverbud program is to offer age-appropriate, fun, and exploratory learning experiences for children in the 5 to 7 age group. This 5-page fact sheet describes the best management practices 4-H faculty and volunteers should use when teaching and interacting with this age group. Written by Amanda Squitieri and Sarah Hensley, and published by the UF Department of 4-H Youth Development, June 2015.